Effective sign language communication among hearing impaired Malaysian students with different cognitive styles - V. Chadra Shakaran a/l V. V. Menon; Fong Soon Fook (Penerbit UMS, 2018)
This quantitative study investigated the effects of E-SignNet on the learning of Malaysian Sign Language among 147 hearing impaired students with different cognitive styles in Malaysia. A quasi-experimental with control group pre-test and post-test design was used in this research. The independent variables were the presentation modes (SLTI, SLI and SLT) and cognitive styles. The dependent variable was the achievement scores, and the covariate was the pre-test scores. The two-way ANCOVA was performed to analyse the effects of cognitive styles (independent variable) on the achievement scores (dependent variable) among the three presentation modes. The results revealed that by using E-SignNet, there were no significant difference in achievement scores among the three presentation modes and cognitive styles.